2023
DOI: 10.1007/s10462-023-10424-4
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning algorithms to forecast air quality: a survey

Abstract: Air pollution is a risk factor for many diseases that can lead to death. Therefore, it is important to develop forecasting mechanisms that can be used by the authorities, so that they can anticipate measures when high concentrations of certain pollutants are expected in the near future. Machine Learning models, in particular, Deep Learning models, have been widely used to forecast air quality. In this paper we present a comprehensive review of the main contributions in the field during the period 2011–2021. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(18 citation statements)
references
References 168 publications
(82 reference statements)
0
7
0
1
Order By: Relevance
“…For instance, all three methods of clustering presented in [2,3] and this study can be applied to the immensely popular task of forecasting air pollution in Beijing [87][88][89]. Unsupervised machine learning holds promise for addressing similar problems in meteorology, pollution control, and other environmental sciences [90].…”
Section: Prelude and Performance: Unsupervised Machine Learning And T...mentioning
confidence: 94%
“…For instance, all three methods of clustering presented in [2,3] and this study can be applied to the immensely popular task of forecasting air pollution in Beijing [87][88][89]. Unsupervised machine learning holds promise for addressing similar problems in meteorology, pollution control, and other environmental sciences [90].…”
Section: Prelude and Performance: Unsupervised Machine Learning And T...mentioning
confidence: 94%
“…Air quality assessment has heavily relied on conventional methods for an extensive period. These traditional methodologies to air quality prediction involve using mathematical and statistical techniques [14]. They typically start with designing a physical model and encoding data using mathematical equations.…”
Section: Literature Surveymentioning
confidence: 99%
“…The authors found that there were more studies focused on pollutants such as O 3 , NO 2 , PM 10 , and PM 2.5 , while fewer studies covered CAQI prediction. We refer interested readers to a comprehensive review [20] of 155 papers that provides a detailed analysis of air quality prediction using ML techniques.…”
Section: Related Workmentioning
confidence: 99%